Comparison of Blood Bacterial Communities in Periodontal Health and Periodontal Disease - Emery, David C.; Cerajewska, Tanya L.; Seong, Joon; Davies, Maria; Paterson, Alex; Allen-Birt, Shelley J.; West, Nicola X. (Frontiers in Cellular and Infection Microbiology, 2021)
The use of Next Generation Sequencing (NGS) techniques has generated a wide variety of blood microbiome data. Due to the large variation in bacterial DNA profiles between studies and the likely high concentrations of cell-free bacterial DNA in the blood, it is still not clear how such microbiome data relates to viable microbiota. For these reasons much remains to be understood about the true nature of any possible healthy blood microbiota and of bacteraemic events associated with disease. The gut, reproductive tracts, skin and oral cavity are all likely sources of blood-borne bacteria. Oral bacteria, especially those associated with periodontal diseases, are also commonly associated with cardiovascular diseases such as infective endocarditis and also have been linked to rheumatoid arthritis and Alzheimer’s disease. Periodontal treatment, dental probing and toothbrushing have been shown to cause transient bacteraemia and oral bacteria from the phyla Firmicutes (e.g.Streptococci) and Bacteroidetes (e.g. Porphyromonas) are found in cardiovascular lesions (CVD). Many studies of blood bacterial DNA content however, find Proteobacteria DNA to be the dominant microbiome component, suggesting a gut origin. Most studies of this type use total DNA extracted from either whole blood or blood fractions, such as buffy coat. Here, using a method that purifies DNA from intact bacterial cells only, we examined blood donated by those with active, severe periodontitis and periodontally healthy controls and show that 43-52% of bacterial species in blood are classified as oral. Firmicutes, consisting largely of members of the Streptococcus mitis group and Staphylococcus epidermidis, were predominant at 63.5% of all bacterial sequences detected in periodontal health and, little changed at 66.7% in periodontitis. Compared to studies using total DNA Proteobacteria were found here at relatively low levels in blood at 13.3% in periodontitis and 17.6% in health. This study reveals significant phylogenetic differences in blood bacterial population profiles when comparing periodontal health to periodontal disease cohorts.